A Descriptive Analysis of Ambiguous Loss and Its Psychological Impact Among College Students - Adinda Annisa Nur Fadhillah; Gian Sugiana Sugara; Anandha Putri Rahimsyah (Journal of Mental Health and Well-Being in Counseling, 2025)
This study aims to describe the level of ambiguous loss among college students. A quantitative approach with a descriptive design was employed. The sample consisted of 277 students selected through purposive sampling. The Ambiguous Loss Inventory Plus (ALI+) was used to identify the forms and levels of ambiguous loss experienced by the participants. The findings indicate that most students fell into the low (43.68%) and moderate (29.24%) categories, while the remaining participants were classified into the high (16.61%) and very high (10.47%) categories. In terms of psychological reactions, the highest scores were observed in the dimensions of intrusive and acute emotions, perceptual distortions and difficulties in adaptation, as well as impacts on the self and social relationships. These results suggest that although the majority of students experience relatively low levels of ambiguous loss, the emotional and cognitive impacts remain notably significant.